The Colour Vocabulary in Fahrenheit 451 by Ray Bradbury and its Russian Translation - Sokolova, Elena N. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2018)
This article is devoted to the comparative analysis of colour vocabulary in Fahrenheit 451 by Ray Bradbury and its Russian translation. The author defines the uniqueness of the world colour picture of the novel as a component of the writer’s individual style referring to the analysis of features functioning in the structure of the literary text. The colour designations used by the author are not only a means of direct colour nomination, they also act as an important component of the poetics of the novel which determines its stylistic identity. Quantitative analysis of the colour vocabulary demonstrates that the work has a specific colour palette, which is related to the key themes of the work and represented by the most frequent black, red, and white colours and their shades in the source and target texts. In addition to adjectives, nouns, verbs, and participles, and even whole phrases of different structure are used to denote colours in the novel. Among the latter, it is important to point out figurative means of “object” nominations of colours containing a hidden simile: such structurally complex nominations contain a lexical unit having an object of the material world as its denotation, acting as a “reference” carrier of the corresponding colour attribute. Analysis of the classic Russian translation by T. N. Shinkar shows that the Russian version of the novel uses more colours than the original text. Moreover, comparative constructions with the colour component are more actively used due to the translator’s desire to convey colour characteristics more accurately, including the ones implied. The article focuses on nonce colour terms used by the author and methods of their translation with the help of various types of translation transformations.